Does tourism experience matter in cultural tourism destinations? Predicting future tourist behavior - Nanggong, Ardiwansyah; Mohammad, Ali (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Cultural tourism, as a niche market in the service-intensive tourism industry, has distinctive characteristics, experiences, and different individual consequences. The primary objective of this study is to explore the underlying substantial dimension of cultural tourism experiences in predicting tourists’ behaviors to stimulate electronic word-of-mouth (e-WoM) and shaping the cultural destination image. A quantitative approach was conducted with PLS-SEM to analyze data for tourists visiting the culture tourism village at Gorontalo, in Indonesia. The bootstrapping procedure is used to test the mediation effect, with direct and indirect effects analyzed. The results indicate that among the various components of the cultural tourism experience, relaxation and learning about the local culture are particularly significant in generating tourist e-wom behavior. The study also acknowledges the crucial role of e-WoM in cultural tourism as a mediator among relaxation, learn local culture, and destination image. Ultimately, these findings emphasize the importance of cultural tourism in showcasing experiences that provide relaxation and new knowledge originating from destinations. This research contributes to an enhanced understanding of the diverse impact of the cultural tourism experience dimension and its consequences for tourist behavior.